2021
DOI: 10.1186/s12935-021-02128-y
|View full text |Cite
|
Sign up to set email alerts
|

DDX52 knockdown inhibits the growth of prostate cancer cells by regulating c-Myc signaling

Abstract: Background DDX52 is a type of DEAD/H box RNA helicase that was identified as a novel prostate cancer (PCa) genetic locus and possible causal gene in a European large-scale transcriptome-wide association study. However, the functions of DDX52 in PCa remain undetermined. The c-Myc oncogene plays a crucial role in the development of PCa, but the factors that regulate the activity of c-Myc in PCa are still unknown. Methods We determined DDX52 protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Further, a characteristic gene-based nomogram was established, which was capable of accurately predicting heart failure risk, with the excellent clinical usability. DDX52 is a type of DEAD/H box RNA helicase, and its suppression exerts an anti-tumor effect (Yu et al, 2021). The DEAH-box RNA helicase DHX15 has been identified as a potential gene for pathological cardiac hypertrophy triggered by excessive exercise (Zhou et al, 2020) and pulmonary arterial hypertension (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a characteristic gene-based nomogram was established, which was capable of accurately predicting heart failure risk, with the excellent clinical usability. DDX52 is a type of DEAD/H box RNA helicase, and its suppression exerts an anti-tumor effect (Yu et al, 2021). The DEAH-box RNA helicase DHX15 has been identified as a potential gene for pathological cardiac hypertrophy triggered by excessive exercise (Zhou et al, 2020) and pulmonary arterial hypertension (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, DDX3 also regulated AR posttranscriptionally by sequestering mRNA, and inhibiting DDX3 was sufficient to reduce AR protein expression and signalling, resensitizing PCa cells to AR signalling inhibitors [ 16 ]. Yu et al [ 17 ] reported that DDX52 knockdown inhibits PCa cell growth by regulating c-Myc signal transduction, and they found that DDX52 has a significant decreasing effect on c-Myc, which promotes the progression of PCa and that c-Myc’s oncogenic potential in PCa cells may rely on DDX52. However, the DDX family comprises at least 35 genes, most of which have not been evaluated for function in PCa, especially in castration-resistant PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Its significance extends from its contribution to the onset and progression of various human ailments. For instance, studies on prostate cancer cells suggest that DDX52 inhibition can effectively retard cancer cell growth by modulating the c-Myc signaling pathway 8 . Findings from a zebrafish model emphasize DDX52’s role as a growth regulator during early developmental stages 9 .…”
Section: Introductionmentioning
confidence: 99%